COVID-19 Vaccine and Active Infection Associated Neuropsychiatric Manifestations in an Adolescent: A Literature Review - Neel Vyas (BJPsych Open)
Aims: The aim of this study is to evaluate the literature for COVID-19 induced psychosis in a child and adolescent population.